Evaluation of Antioxidant Activity of Crataegus Species Collected from Different Regions of Turkey - (:unkn) unknown (ACG PUBLICATIONS, 2012)
Crataegus species (Rosaceae), known as Howthorn have found special medicinal use for the treatment of mild heart diseases. This work aims to measure the antioxidant capacities of various Crataegus species growing in Turkey. In this study, the flowers and leaves from 52 samples belonging to 17 taxa of 14 Crataegus species naturally growing in Turkey have been investigated for their antioxidant activity/capacity. Four different methods (CUPRAC, FRAP, ABTS/Persulfate and Folin: FCR assays) were used for determination of the antioxidant capacities of the samples. The leaves and the flowers of the plants were studied separately. Samples representing the same species collected from different locations were studied separately. The results have indicated that the samples differing by some minor morphological characteristics exhibit considerably different antioxidant capacities. Among the flower samples, the most effective species was C. x sinaica Boiss. nothosubsp. sinaica and among the leaf samples C. pentagyna Waldst and Kit. ex. Willd. were the most active. Generally, C. monogyna Jacq. samples have exhibited markedly high antioxidant activity. Moreover, the species collected from Bolu district (surrounded by several forests and lakes) have shown significantly high activity regardless of the species differences among the samples.
Keywords: Crataegus; antioxidant capacity assays; CUPRAC; ABTS; FRAP; Folin; PHENOLIC-COMPOUNDS; CAPACITY ASSAYS; ROSACEAE; HAWTHORN; POWER; FRAP; FLAVONOIDS; MEDICINE